DOI: 10.11606/t.5.2008.tde-12022009-134520
|View full text |Cite
|
Sign up to set email alerts
|

Adaptação e validação da versão em português da escala graduada de dor crônica para o contexto cultural brasileiro

Abstract: Adaptação e validação da versão em português da escala graduada de dor crônica para o contexto cultural brasileiro / Eduardo Sawaya Botelho Bracher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1
7

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 82 publications
(177 reference statements)
0
7
1
7
Order By: Relevance
“…However, when the value is less than 0.7, the questionnaire most likely addresses a construct that is different to the one that it seeks to measure, whereas when the alpha is greater than 0.9, there is an extremely high correlation due to item redundancy. 34,35 For three of the lifestyle factors, the value of Cronbach's alpha was less than 0.7 in the present study.…”
contrasting
confidence: 64%
“…However, when the value is less than 0.7, the questionnaire most likely addresses a construct that is different to the one that it seeks to measure, whereas when the alpha is greater than 0.9, there is an extremely high correlation due to item redundancy. 34,35 For three of the lifestyle factors, the value of Cronbach's alpha was less than 0.7 in the present study.…”
contrasting
confidence: 64%
“…Concerning the construct analysis of the scale in Brazilian parents, the initial analysis revealed three factors with variances of 57.2%, which is considered good (14) ( Table 2). The scale items demonstrated good grouping among the three a priori defined subscales of the PSS:NICU.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Bracher (14) demonstrated that, out of 21 studies published in 2007 about the cultural adaptation of instruments, 13 used the method Guillemin et al (11) proposed. The internal consistency of the PSS:NICU scale for use in Brazilian parents is similar to the findings in original validation studies of the scale in English, in which the sights and sounds subscale obtained a Cronbach's alpha (5) .…”
Section: Discussionmentioning
confidence: 99%
“…We used an instrument with sociodemographic and clinical variables to characterize the sample. To evaluate the pain, the graduated scale for chronic pain * was adopted, adapted, and validated for Brazil [15]. This scale is made up of eight items that assess the frequency, intensity, and disability linked to pain.…”
Section: Data Collection and Instrumentmentioning
confidence: 99%
“…From question two (02) to eight (08), the questions aid the individual to remember the pain of the past three months, marking on a Likert scale of 10 points [15].…”
Section: Data Collection and Instrumentmentioning
confidence: 99%